(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Effective bookkeeping procedures are essential for financial management and decision- making in any organization. This study aimed to identify the challenges encountered by the finance department in bookkeeping procedures and propose recommendations to address these challenges. The study found that respondents encountered challenges related to recording and keeping records in the finance department but did not encounter significant challenges related to retrieving records. Respondents strongly agreed that bookkeeping is important in their procedures for recording documents, keeping records, and retrieving records. Most respondents preferred bookkeeping training and using bookkeeping software as a solution to the challenges encountered. The researchers recommend implementing several measures to improve bookkeeping procedures in the finance department at ABC College. These measures include providing training on best practices for data entry and investing in bookkeeping software with automatic updates. To implement these recommendations, several proposed outputs include a comprehensive bookkeeping training program covering data entry best practices, bookkeeping skills, and bookkeeping software training. The finance department should also consider implementing a backup generator or alternative power source to prevent data loss. Budgetary constraints should also be taken into account when deciding on the best course of action.